Experiences of interventions aiming to improve the mental health and well‐being of children and young people with a long‐term physical condition: A systematic review and meta‐ethnography. (16th August 2019) - Shaw, Liz; Moore, Darren; Nunns, Michael; Thompson Coon, Jo; Ford, Tamsin; Berry, Vashti; Walker, Erin; Heyman, Isobel; Dickens, Christopher; Bennett, Sophie; Shafran, Roz; Garside, Ruth
Abstract: Background: Children and young people with long‐term physical health conditions are at increased risk of experiencing mental health and well‐being difficulties. However, there is a lack of research that explores the experiences of and attitudes towards interventions aiming to improve their mental health and well‐being. This systematic review seeks to address this gap in the literature by exploring what children and young people with long‐term conditions, their caregivers, and health practitioners perceive to be important aspects of interventions aiming to improve their mental health and well‐being. Methods: An information specialist searched five academic databases using predefined criteria for qualitative evaluations of interventions aiming to improve the mental health or well‐being of children with long‐term physical conditions. Reviewers also performed supplementary citation and grey literature searches. Two reviewers independently screened titles, abstracts, and full texts that met the inclusion criteria and conducted data extraction and quality assessment. Meta‐ethnography was used to synthesize the findings. Results: Screening identified 60 relevant articles. We identified five overarching constructs through the synthesis: (a) Getting In and Staying In, (b) Therapeutic Foundation, (c) Social Support, (d) A Hopeful Alternative, and (e) Empowerment. The line of argument that links these constructs together indicates that when interventions can provide an environment that allows young people to share their experiences and build empathetic relationships, it can enable participants to access social support and increase feelings of hope and empowerment. Conclusion: These findings may provide a framework to inform the development of mental health interventions for this population and evaluate existing interventions that already include some of the components or processes identified by this research. Further research is needed to establish which of the constructs identified by the line of argument are most effective in improving the mental well‐being of young people living with long‐term conditions.